2022
DOI: 10.1049/tje2.12181
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fuel price increasing policies on fuel smuggling and acceptance of green cars: A case study of Iran

Abstract: This paper investigates a study on the efforts made by Iranian government to carry out the Kyoto protocol obligations (reducing pollution by about 54% by 2030). However, the devaluation of the national currency because of sanctions, prohibition of transactions, and a decrease in oil revenues and derivatives has caused problems in achieving this goal. Hence, on 15 November, 2019, Iranian Government decided to increase the fuel price by about 300% to simultaneously reduce environmental pollution and fuel smuggli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 39 publications
0
0
0
Order By: Relevance
“…In addition, for people whose car is hybrid, the increase in ATN travel cost will have a higher negative efect on choosing the ATN option compared to those whose car is gasoline by 8%. Since some research conducted both in developed and developing countries indicated that one of the reasons people use hybrid cars is their lower fuel costs compared to gasoline cars and not environmental concerns [58][59][60], and these people are likely more sensitive to the cost compared to gasoline car owners. As a result, this sensitivity has caused the increase in the ATN travel cost to have a more negative efect on them than the owners of gasoline cars.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, for people whose car is hybrid, the increase in ATN travel cost will have a higher negative efect on choosing the ATN option compared to those whose car is gasoline by 8%. Since some research conducted both in developed and developing countries indicated that one of the reasons people use hybrid cars is their lower fuel costs compared to gasoline cars and not environmental concerns [58][59][60], and these people are likely more sensitive to the cost compared to gasoline car owners. As a result, this sensitivity has caused the increase in the ATN travel cost to have a more negative efect on them than the owners of gasoline cars.…”
Section: Resultsmentioning
confidence: 99%